The fiscal impact of immigrants in Austria - A generational accounting analysis - Karin Mayr (Johannes Kepler University of Linz, Department of Economics, 2004)
In this paper, we employ generational accounting to analyse the inter-temporal stance of Austrian public finance in 1998 as well as the inter-temporal fiscal impact of immigration to Austria. Immigrants affect inter-temporal fiscal balance in essentially two ways. Firstly, they have a demographic effect in enlarging the population (and thus the tax base) and in altering its age- (and gender-) composition. Secondly, they change the fiscal characteristics of age cohorts due to a representative immigrant exhibiting higher or lower tax and transfer payments than a representative native of the same age and gender. The overall fiscal effect of immigration is found positive, under the assumption that the age and fiscal characteristics of future immigrants resemble those of the current immigrant population in Austria. This is due to a favourable age composition and lower per capita net transfer receipts during retirement age, which compensates for lower per capita net tax payments during working age. However, immigration is not likely to achieve inter-temporal fiscal balance, even if immigration increases or migrants are screened by skill or age.
Keywords: F22; H61; E66; 330; immigration; generational accounting; fiscal imbalance; Intergenerative Belastungsrechnung; Einwanderung; Öffentliche Finanzwirtschaft; Öffentlicher Haushalt; Österreich